Could inherited predisposition drive non-obese fatty liver disease?: results from German tertiary referral centers - Krawczyk, Marcin; Bantel, Heike; Rau, Monika; Schattenberg, Jörn Markus; Grünhage, Frank; Pathil-Warth, Anita; Demir, Münevver; Kluwe, Johannes; Böttler, Tobias; Weber, Susanne Nicole; Geier, Andreas; Lammert, Frank (Journal of human genetics, 2018)
Non-alcoholic fatty liver disease (NAFLD) is frequent among obese individuals with metabolic syndrome. Variants PNPLA3 p.I148M, TM6SF2 p.E167K and MBOAT7 rs641738 are associated with higher liver fat contents. Here we analyzed 63 biopsied non-obese, non-diabetic patients with NAFLD (39 men, age: 20-72 years) recruited within the German NAFLD CSG program. The frequencies of the PNPLA3, TM6SF2 and MBOAT7 polymorphisms were compared with the remaining patients in the NAFLD CSG cohort and with a control population (n = 174). Serum CK18-M30 was measured by ELISA. In non-obese NAFLD patients, the frequency of the PNPLA3 p.I148M allele (74.6%), but not of the TM6SF2 or MBOAT7 polymorphisms, was significantly (P < 0.05) higher as compared to the other patients in the NAFLD CSG cohort (54.9%) or controls (40.2%). The presence of the minor PNPLA3 p.I148M risk allele increased the risk of developing NAFLD (OR = 3.29, P < 0.001) and was associated with higher steatosis, fibrosis, and serum CK18-M30 levels (all P < 0.05). According to the population attributable fraction (PAF), 49.8% of NAFLD cases could be eliminated if the PNPLA3 mutation was absent. The MBOAT7 polymorphism was more frequent (P = 0.019) in patients with severe hepatic steatosis. In conclusion, PNPLA3, and to a lesser extent, MBOAT7 variants are associated with NAFLD risk and modulate liver injury in non-obese patients without diabetes.
Gesehen am 28.10.2019